Developmental Studies of the Gastric Junctions of the Post hatching Muscovy Duck (Cairina moschata) - Fatma Abbass Madkour (South Valley University, 2018)
The current study was carried out on 24 apparently healthy post-hatching Muscovy ducks of both sexes ranging from 1-60 days old. They were divided into 5 age groups to investigate the development of the junctions of the stomach; esophago-proventricular junction, proventriculo-gizzard junction (Isthmus gastris) and ventriculo-duodenal junction by using light and scanning electron microscopy. The longitudinal folds of the esophago-proventricular junction were separated by longitudinal grooves and they were crossed by thin transverse ridges; some of the longitudinal folds were branched toward the proventriculus at 60 days old. At one day old, the lymphoid infiltrations were observed in the lamina propria at the esophago-proventricular junction. With the advancement of the age, abundant diffused lymphoid infiltration and esophageal tonsil were observed. In all age groups, the cuticle covering of the mucosa at proventriculus-gizzard junction increased in thickness toward the gizzard. Moreover, in one day old duckling, the proventricular glands were observed underneath the gizzard tubular glands, these glands were become well developed at 60 days old. The lamina propria of the gizzard-duodenal junction showed slight lymphatic infiltration at one day old age. Lymphatic infiltration and more lymphatic aggregations were abundant at 7-15 days. While between 30-60 days age, lymph nodules were distinct. Numerous endocrine cells were also observed in mucosa of the gizzard-duodenal junction.